2019
DOI: 10.1080/17446651.2019.1657008
|View full text |Cite
|
Sign up to set email alerts
|

Ospemifene for the treatment of menopausal vaginal dryness, a symptom of the genitourinary syndrome of menopause

Abstract: Introduction: Vulvovaginal atrophy (VVA), a component of the genitourinary syndrome of menopause, is a progressive condition due to decline in estrogen leading to vaginal and vulvar epithelial changes. Accompanying symptoms of dryness, irritation, burning, dysuria, and/or dyspareunia have a negative impact on quality of life. Ospemifene is a selective estrogen receptor modulator (SERM) approved by the FDA for moderate to severe dyspareunia and vaginal dryness due to postmenopausal VVA. Areas covered: PubMed wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…All studies showed some beneficial response to therapy, although results were variable and the authors concluded that tamoxifen or a combination of tamoxifen and progestin might be the best choice when selecting second-line hormonal treatment. In subsequent studies, the SERM Ospemifene has been shown as an effective in treatment of vaginal symptoms in postmenopausal women (Archer et al 2019) and only acts as an agonist in endometrium in high doses. The SERD fulvestrant/faslodex (Table 2) has been investigated as a treatment for endometrial cancer in phase I/II trials, although well-tolerated, it has low oral bioavailability and further trials are needed (Bogliolo et al 2017).…”
Section: Targeting Oestrogen Receptors In Endometrial Disordersmentioning
confidence: 99%
“…All studies showed some beneficial response to therapy, although results were variable and the authors concluded that tamoxifen or a combination of tamoxifen and progestin might be the best choice when selecting second-line hormonal treatment. In subsequent studies, the SERM Ospemifene has been shown as an effective in treatment of vaginal symptoms in postmenopausal women (Archer et al 2019) and only acts as an agonist in endometrium in high doses. The SERD fulvestrant/faslodex (Table 2) has been investigated as a treatment for endometrial cancer in phase I/II trials, although well-tolerated, it has low oral bioavailability and further trials are needed (Bogliolo et al 2017).…”
Section: Targeting Oestrogen Receptors In Endometrial Disordersmentioning
confidence: 99%
“…Selective estrogen receptor modulators such as Ospemifine can act as estrogen agonists or antagonists on target tissues depending on binding and activation of intracellular estrogen receptor alpha, beta, or both 40 . Ospemifene binds to both estrogen receptors with equal affinity and is approved by North American and European agencies for treatment of postmenopausal vaginal dryness in women who are not candidates for local vaginal estrogen therapy 41 . Ospemifene acts as an estrogen receptor agonist in the vulva and vagina, as a partial agonist in the uterus and bone, and has neutral to antagonistic effects in the breast 41 .…”
Section: Gonadal Insufficiencymentioning
confidence: 99%
“…Daily treatment with 60 mg orally improves vaginal dryness and dyspareunia. Safety data are available on its administration for 12 months [144][145][146].…”
Section: Ospemifenementioning
confidence: 99%